(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article analyzes the didactic foundations of using the STEAM (Science, Technology, Engineering, Arts, Mathematics) approach in teaching the subject of “Electrical Engineering” in higher education institutions. The author, in contrast to traditional teaching methods, highlights the role of interdisciplinary integration in the development of engineering thinking and creative abilities of students. The article proposes a methodology for connecting electrical engineering laws with modern technologies and design elements on the example of specific projects.